2007
DOI: 10.1007/s10886-007-9306-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biosynthetic Studies of the Hydrocarbon Sex Pheromone in Utetheisa ornatrix

Abstract: The type II class of sex pheromones found in moths is composed of polyene hydrocarbons and their epoxides. Analysis of Utetheisa ornatrix females by gas chromatography-mass spectrometry and measurement of responses of male moths by coupled gas chromatography-electroantennogram detection confirmed the presence of large amounts of (Z,Z,Z)-1, 3,6,3,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] and smaller amounts of (Z,Z,Z)-3,6,9-heneicosatriene (3,6,9-21:Hy). Both compounds were detected in pheromone gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Using in vivo labeling, we first demonstrated that the biosynthesis of 1,Z3,Z6,Z9-19:H is initiated from the diet-derived linolenic acid. Linolenic acid is also reported to serve as initial precursor for the biosynthesis of hydrocarbon pheromones in the pyralid wax moth Galleria mellonella (L.) (Stanley-Samuelson et al, 1987) and the arctiid moths Estigmene acrea (Drury) and Phragmatobia fuliginosa (L.) (Rule and Roelofs, 1989), as well as Utetheisa ornatrix (L.) (Choi et al, 2007). This supports that most polyunsaturated hydrocarbon pheromones in various moth families are likely to occur via chain elongation, desaturation and decarboxylation of linolenic acid Wang et al, 2010a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Using in vivo labeling, we first demonstrated that the biosynthesis of 1,Z3,Z6,Z9-19:H is initiated from the diet-derived linolenic acid. Linolenic acid is also reported to serve as initial precursor for the biosynthesis of hydrocarbon pheromones in the pyralid wax moth Galleria mellonella (L.) (Stanley-Samuelson et al, 1987) and the arctiid moths Estigmene acrea (Drury) and Phragmatobia fuliginosa (L.) (Rule and Roelofs, 1989), as well as Utetheisa ornatrix (L.) (Choi et al, 2007). This supports that most polyunsaturated hydrocarbon pheromones in various moth families are likely to occur via chain elongation, desaturation and decarboxylation of linolenic acid Wang et al, 2010a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent evidence suggests that even-numbered chains probably are produced by the same series of 2-carbon chain extension steps, then α-oxidation and loss of one carbon, followed by loss of a second carbon as CO or CO 2 by an oxidative mechanism (Goller et al 2007). In some cases, further desaturation also occurs somewhere in the pathway to produce compounds such as the tetraene hydrocarbon pheromones of the arctiid moth Utetheisa ornatrix (Linnaeus) (Choi et al 2007) and the geometrid moth Operophtera brumata (L.) (Zhao and Löfstedt, unpublished data). The newly formed polyene skeletons then are transported through the hemolymph by lipophorin carriers from the oenocytes to the pheromone gland (Wei et al 2004; Matsuoka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to studies published to date, pheromone biosynthesis activating neuropeptides (PBANs) are not involved in the production of unsaturated hydrocarbon pheromone components in the arctiid moth U. ornatrix (Choi et al 2007) or the geometrid moth Ascotis selenaria cretacea (Butler) (Wei et al 2004), but they are involved in the epoxidation of these hydrocarbons in the pheromone gland, for those species that use epoxide pheromones alone or in combination with unsaturated hydrocarbons (e.g., the lymantriid moth Lymantria dispar L. (Jurenka et al 2003) and the geometrid moth A. selenaria cretacea B. (Ando et al 1997; Wei et al 2004)).…”
Section: Introductionmentioning
confidence: 99%
“…152 Other than serving as ''on'' or ''off'' switches for mating, attrac-153 tive pheromones can also function as nuptial gifts and signals that 154 convey information about the quality of the sender. For example, 155 pyrrolizidine compounds, which are toxic substances for many ani-156 mals, are used by Arctiid moths in some cases as attractants for…”
mentioning
confidence: 99%
“…Several desaturases exhibit 539 specificity for monounsaturated substrates [149][150][151][152][153][154]. Lastly, sev-540 eral desaturases in Lepidoptera are known to produce triene pher-541 omone components, also using linoleic acid as a substrate [89,155]. …”
mentioning
confidence: 99%